Development of edible films based on pectin and essential oil extracted from orange (Citrus sinensis) peel using a central composite design - Liliana Castillo-Rodríguez; Aleida-Selene Hernández-Cázares; Marlon Rojas-López; Juan-Valente Hidalgo-Contreras; Aurelio López-Malo; María-Antonieta Rios-Corripio (CyTA - Journal of Food, 2025)
This study formulated edible films (EFs) from pectin and orange (Citrus sinensis) peel essential oil. A central composite design was used to obtain an optimized EFs. Pectin was extracted using the acid hydrolysis method, and essential oil was extracted using the steam distillation method. The resulting optimal composition was 1.5% w/w pectin, 0.75% w/w glycerol, and 1.5% v/v essential oil. The EFs were characterized with respect to its thickness, color, opacity, moisture content, solubility, water vapor permeability (WVP), tensile strength (Ts), and Young’s modulus (YM). The optimized EFs were evaluated for their antifungal effect against Fusarium solani and showed lower WVP, thickness, opacity, and solubility values, higher Ts and YM values, and inhibition of Fusarium solani. FTIR showed interactions between the components of the optimized EFs. It is concluded that pectin and orange peel essential oil are a promising option for the development of edible films that provide food safety.